El Proceso Educativo Fiscal Y Su Influencia En Los Resultados De Las Pruebas Ser Estudiante, Del Séptimo Año De Educación General Básica, En El Cantón Guaranda, Ecuador - René Villacrés Borja; Mónica Bonilla Manobanda; Javier García López; Fidel Castro Bério (European Scientific Journal, ESJ, 2017)
The Being Student tests recognize the characteristics of the students of the National Education System in relation to their knowledge. It allows the evaluated ones to know what situation they entail in the learning standards of each level, and was issued by the Ministry of Education. This therefore is aimed at knowing the level of learning achieved according to the Quality Standards issued by the Ministry of Education for this level. It is also in relation to their knowledge and reasoning skills. These instruments, according to their results, have allowed the Social Categorization of Educational Units at the National level, evidencing that the Educational Institutions of the Bolivar Province, especially the Guaranda Canton, are not within the first places of this social recognition. As a result, this implies that the fiscal education process up to this level is not meeting the standards of educational quality within the domain of knowledge. The objective of this study is to characterize how the fiscal education process influences the results of the student tests at the seventh year of basic general education. The unit of analysis is the educational process and the unit of observation is a student for each subject of each fiscal institution studied. The present research uses both quantitative and qualitative approach. This type of research is a documentary, bibliographical, and field research since it analyzed the notebooks of theoretical notes of duties, use of the official books for the academic period 2016 - 2017, and corrections of written tests and their structure which serves as the key elements to determine and conceptualize the academic process.